Trajectories of De Ritis ratio with risk of hepatocellular carcinoma and liver-related mortality following direct-acting antivirals for HCV: a retrospective longitudinal study up to 10 years. (30th November 2022) - Jia, Linna; Yue, Ming; Wang, Yidi; Ye, Xiangyu; Zou, Yanzheng; Zhang, Amei; Feng, Yue; Xia, Xueshan; Yang, Sheng; Yu, Rongbin; Huang, Peng
Abstract: The De Ritis ratio has good diagnostic accuracy in patients with chronic viral liver disease. However, its prognostic utility has remained controversial. This study was to identify different trajectories of De Ritis ratio in those hepatitis C patients cured and analyze the relationship between trajectory groups and risk of hepatocellular carcinoma (HCC) with liver-related mortality by the retrospective cohort study. This retrospective longitudinal cohort included 1241 patients with hepatitis C who underwent antiviral therapy since follow-up in 2012. De Ritis ratio trajectories were identified by the latent class growth mixed model. Patients were grouped into subgroups by De Ritis ratio according to longitudinal trajectories. The endpoints were HCC and liver-related mortality. Three distinct trajectory groups were characterized for serum De Ritis ratio: low-stable, middle-stable and high-rising. Fifty-one HCC and 11 liver-related mortality were recorded and tracked. Compared to the low-stable group, the adjusted hazard ratios (HRs) and 95% confidence interval (CI) associated with HCC and liver-related mortality were 2.02 (1.12 to 3.63), 9.36 (3.61 to 24.29), for the middle-stable, and high-rising group, respectively. Notably, the high-rising trajectory group still had prognostic significance after adjusting for preoperative levels. Likewise, for the high-rising trajectory group of sustained virological response, the HRs (95% CI) were 2.85 (1.03 to 10.75) for HCC and liver-related mortality, and in patients with cirrhosis, the HRs (95% CI) were 3.44 (1.64 to 7.19) and 4.35 (1.27 to 14.84) in the middle-stable trajectory group and the high-rising trajectory group, respectively. The dynamic measurements of De Ritis ratio are recommended to monitor the prognosis of Hepatitis C patients. Abstract : De Ritis ratio had three longitudinal patterns, characterized by low-stable, middle-stable, and high-rising. The middle-stable and high-rising groups were associated with increased risks of HCC and liver-related mortality comparing to the low-stable group. And the high-rising group associations with HCC and liver-related mortality was significant, independent of existing prognostic factors. Graphical abstract: